Analysis of the stability of InGaN/GaN multiquantum wells against ion beam intermixing. (1st October 2015) - Redondo-Cubero, A; Lorenz, K; Wendler, E; Magalhães, S; Alves, E; Carvalho, D; Ben, T; Morales, F M; García, R; O'Donnell, K P; Wetzel, C
Abstract: Ion-induced damage and intermixing was evaluated in InGaN/GaN multi-quantum wells (MQWs) using 35 keV N + implantation at room temperature . In situ ion channeling measurements show that damage builds up with a similar trend for In and Ga atoms, with a high threshold for amorphization. The extended defects induced during the implantation, basal and prismatic stacking faults, are uniformly distributed across the quantum well structure. Despite the extremely high fluences used (up to 4 × 10 16 cm −2 ), the InGaN MQWs exhibit a high stability against ion beam mixing.